Pengajaran Teknik Manual Menggambar Bentuk Pada Siswa Kelas IX Labschool Jakarta - syahrani, farah (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
This research aims to assess the ability of grade IX students at SMP Labschool Jakarta in drawing with colored pencils and the impact of implementing Project-based Learning (PjBL) approach in cultural arts education. The results indicate that students face challenges in manual drawing and have limited understanding of proper drawing techniques. Therefore, it is essential to provide instruction on manual drawing techniques to establish a strong foundation and reduce dependence on digital technology. The application of PjBL in cultural arts education yields significant positive effects, enhancing students' creativity, understanding of cultural art concepts, collaboration among students, motivation to learn, and valuable hands-on experiences. The findings of this research support the importance of teaching manual drawing techniques in developing students' artistic skills and creativity. This study has several implications, including the development of understanding of colored pencil drawing techniques, introduction of new art tools, and the strengthening of the fundamentals of visual arts for the future development of digital art potential.